Electropolishing of superconducting cavities for quantum memory applications - BIZNÁROVÁ, JANKA (My University, 2020)
In this thesis, the effect of electrochemical polishing on the internal quality factor Qi of superconducting resonant cavities, proposed to act as quantum memories, is investigated. The resonant cavities are shaped as /4 resonators with two different outer waveguide lengths, 35mm and 50mm. Cavities of both lengths are fabricated from aluminium alloys of two different purities: a 6081 alloy with a 96.3-98.6% aluminium content, and a 4N alloy with a 99.99% aluminium content. Cavities fabricated from the 4N alloy exhibit higher Qi values than the 6081 Al cavities, both as machined and after several rounds of treatment consisting of chemical etching and annealing, showing the influence of material purity on the quality factor of the resonator. The electropolishing process implemented in this work has a positive impact on the Qi of the short cavities, and an adverse effect on the Qi of the longer cavities. This suggests that the geometry of the electropolishing set-up used here is not optimal for polishing the longer cavities. The electropolished long cavities display a decrease in low-power Qi from 12.9 × 106 to 9.9 × 106 for the 6081 alloy, and from 77 × 106 to 25 × 106 for the 4N aluminium. The electropolished short cavities display an increase in low-power Qi from 5.85 × 106 to 11.5 × 106 for the 6081 alloy, and from 29 × 106 to 94 × 106 for the 4N aluminium. Both short cavities show an increase of the power dependence of Qi after electropolishing, hinting at an increased dominance of the TLS loss path to the overall energy loss.
Keywords: superconducting resonator, resonant cavity, superconducting cavity, electropolishing, quality factor, quantum memory